A large-scale wind turbine model installed on a floating structure: experimental validation of the numerical design - F. Taruffi; S. Di Carlo; S. Muggiasca; M. Belloli (Wind Energy Science, 2023)
In the field of floating wind energy, large-scale wind turbine models deployed in natural environments represent a key link between small-scale laboratory tests and full-scale prototypes. While implying smaller cost, design and installation effort than a full-scale prototype, large-scale models are technologically very similar to prototypes, can be tested in natural sea and wind conditions, and reduce by a consistent amount the dimensional scaling issues arising in small-scale experiments. In this framework the presented work report the aerodynamic and control system assessment of a 1:15 model of the DTU 10 MW wind turbine installed on a multipurpose-platform model for fish farming and energy production. The model has operated for 6 months in a natural laboratory and has been exposed to fully natural and uncontrolled environmental conditions. Assessment is performed in terms of rotor thrust force and power controller parameters such as rotor speed, blade pitch and rotor power as a function of incoming wind speed.